OPTIMALISASI PEMBELAJARAN MENDALAM SEBAGAI STRATEGI INOVATIF BERBASIS KONSTRUKTIVISME DALAM MENINGKATKAN KEMAMPUAN MENULIS MURID SECARA KRITIS, KREATIF, DAN REFLEKTIF - Aulia, Arnia; Nurhikmah; Nurfadillah; Candra Dewi, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing is a crucial competency that involves higher-order thinking processes. However, Indonesian students still face significant challenges, such as difficulty generating ideas, irregular sentence structures, and the influence of informal social media language. This study aims to explain the role of deep learning as an innovative, constructivist-based strategy in improving students' critical, creative, and reflective writing skills. This study employed a literature review method by analyzing various academic literature, research reports, and scientific articles published between 2017 and 2026. Data were obtained from Google Scholar and Taylor & Francis Online databases through systematic analysis. The results show that deep learning effectively overcomes these barriers by prioritizing conceptual understanding, interconnections between materials, and the application of knowledge in real-world situations. This approach transforms the learning process into a meaningful, mindful, and joyful experience, directly impacting students' higher-order thinking skills. Furthermore, the integration of digital technology into deep learning supports collaborative writing and independent learning. In conclusion, deep learning is an important pedagogical innovation that not only improves the quality and technical structure of writing, but also shapes critical character and adaptive literacy skills in facing the challenges of the 21st century